Teff growth and yield response to blended fertilizer type and rate in Debub Ari and Bena Tsemay Districts, Southwestern Ethiopia - Malla, Merdikios; Tesema, Genanaw; Animaw, Yenesew (International Journal of Agricultural Research, Innovation and Technology, 2022)
Depleting of soil fertility, soil organic matter, macro-and micro-nutrients and crop nutrient imbalances are among the primary biophysical limitations that reduce the production of teff. The experiment was conducted to evaluate teff response to blended fertilizer types and rates in Debub Ari and Bena Tsemay districts. Control, Recommended NP, 3 dosages of NPS and NPSB blended fertilizer rates each were used that is laid out in RCBD following three replication. The full dose of blended and P fertilizers was applied at planting and urea was applied in two splits. The result was revealed that application of 200 kg ha-1 NPSB + 127 kg ha-1 Urea resulted in the highest grain yield of 2299.5 kg ha-1 in Debub Ari and 200 kg ha-1 NPS + 117 kg ha-1 Urea gives 1809.2 kg ha-1 in Bena Tsemay, while the lowest grain yield was recorded from the nil in both districts. However, the highest economic return was obtained in response to the application of 64 kg ha-1 N + 20 kg ha-1 P in both districts. Application of 64 kg ha-1 N + 20 kg ha-1 P gives 57.24% and 14.42% yield increment in Debub Ari and Bena Tsemay, respectively; also 54.47% and 7.57% increment in economic return in Debub Ari and Bena Tsemay in the same order over the control. Application of 64 kg ha-1 N + 20 kg ha-1 P was recommended for the production of teff on the study area and similar agro-ecologies, as it was optimum for improving teff production. Further investigation should be done on plant nutrient uptake and using efficiency and grain quality. Int. J. Agril. Res. Innov. Tech. 12(1): 145-154, June 2022